Long-term clinical outcomes of [177Lu]Lu-DOTATATE in patients with metastatic neuroendocrine tumors - Iqbal, Sabah; Zhuang, Eric; Raj, Moses; Bahary, Nathan; Monga, Dulabh K. (Frontiers in Oncology, 2024)
The incidence of gastroenteropancreatic neuroendocrine tumors has been rising and these tumors are usually only diagnosed at a metastatic stage. Present first line treatments include somatostatin analogs, targeted therapies and peptide receptor radionuclide therapy. The Lutetium-177 [¹⁷⁷Lu] based radiotracer [¹⁷⁷Lu]Lu-DOTATATE has only been approved as first-line treatment of metastatic midgut NETs however its efficacy as a third line or above treatment in patients with non ileal primaries has not been tested. In our study, we identified 25 patients with histologically confirmed well-differentiated metastatic neuroendocrine tumors and administered [¹⁷⁷Lu]Lu-DOTATATE as a second line, third line and fourth line treatment. Our study demonstrated a notable response in patients with non-ileal primaries and heavily pretreated disease, warranting further studies for additional cycles of treatment.